WAIS Divide Ice-Core Aerosol Records from 1.5 to 577 m - McConnell, Joseph (IEDA: US Antarctic Program Data Center, 2017)
A state-of-the-art continuous ice core analytical system was used to analyze samples from ~1.5 to ~577 m depth in the recently collected WAIS Divide deep ice core from West Antarctica. Interpretation of these records and publication of findings is ongoing.